The Prevalence of Non-albicans Candida and Candida Mixed-species in Vulvovaginal Candidiasis in Northeast Iran - Batoul Jannati; Arash Pourdad; Ali Izadjoo; Hossein Zarrinfar; Mohammad Javad Najafzadeh; Abdolmajid Fata (Clinical and Experimental Obstetrics & Gynecology)
Background: Vulvovaginal candidiasis (VVC) is a prevalent infectious disease that affects the majority of women. While Candida albicans is the most common cause of VVC, the prevalence of non-albicans species is increasing, and mixed infections have made treatment more challenging. This study aimed to identify Candida species and detect mixed infections in women with VVC in a tropical region of northeastern Iran, employing the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Methods: In the prospective study, a total of 270 specimens of vaginal discharge were collected using sterile swabs from patients suspected of having VVC. After extracting DNA from Candida colonies, the genome was amplified using PCR with specific primers. Species identification was conducted through PCR-RFLP analysis of the ribosomal DNA internal transcribed spacer (ITS) regions, using the MspI restriction enzyme. Results: Out of the 270 specimens suspected of VVC, 167 tested positive for Candida cultures. Among these positive Candida cultures, Candida species were identified in 150 specimens, with 44 (29.3%) showing evidence of mixed Candida infections. The species of Candida in 17 specimens were not identified. Out of the 190 identified Candida isolates included, the distribution was as follows: 85 (44.8%) C. albicans, 39 (20.5%) C. glabrata, 28 (14.7%) C. guilliermondii, 11 (5.8%) C. kefyr, 11 (5.8%) C. parapsilosis, 8 (4.2%) C. tropicalis, and 8 (4.2%) C. krusei. The mixed Candida species combinations observed were as follows: C. albicans/C. guilliermondii 26 (65%), C. albicans/C. kefyr 4 (10%), C. parapsilosis/C. glabrata 4 (10%), C. parapsilosis/C. tropicalis 4 (10%), C. krusei/C. tropicalis 2 (5%), C. albicans/C. parapsilosis 1 (2.5%), C. albicans/C. krusei 1 (2.5%), C. glabrata/C. guilliermondii 1 (2.5%), and C. kefyr/C. tropicalis 1 (2.5%). Conclusions: In women with VVC in the tropical region of northeastern Iran, the prevalence of clinical non-albicans species is higher than that of C. albicans. Furthermore, there is a notable high prevalence of clinical specimens containing mixed Candida infections.